Sexually Transmitted Infections in A Tertiary Hospital of Kathmandu: A Retrospective Study - Sushil Paudel; Niraj Parajuli; Sudip Dahal; Sudarshan Paudel (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Sexually transmitted infections (STIs) are the diseases that are transmitted by sexual contact if a partner is infected with agent known to cause infection of genitalia. This group of diseases pose a huge public health problem. This study aims to provide an insight on the prevalence of STIs in a tertiary care center dedicated to civil servants.